(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In regard with designing software, users play key role. In order to design software, it is necessary to observe standard principles of designation, using templates and using modern methods. Over the decades, using development methods, XP and one of the XP methodologies of paired programming used to design software. These methods have been designed for purpose of enhancing quality of product and rapidresponse to need of market and customer and overcoming weaknesses of traditional methods based on long-term programming and waterfall method. Therefore, every programmer and developer can pass a series of processes for constructing computer software. The processes can be changed daily and efficient processes maynot be effective and useful; although they can be considered as process. The main objective of the present study is multi-factor analysis of pair programming based on PSP methodology. Practical and analytical methodand two PSP methods have been applied for investigations.